On the “Mockness” of Mock Juries: Real versus Mock Juries as Conversational Forms - Manzo, John F. (International Journal of Criminology and Sociology, 2019)
This paper is an analysis of real versus simulated, or “mock,” juries. It is specifically focused on similarities and differences between the two forms of group-based deliberation with respect to the content and organization of deliberative talk. Via analysis of transcript from six deliberations—two real and four mock—the value of mock juries as an investigative tool is assessed based not on the relationship between “input” variables, such as the nature of the case, the sociodemographic or sociometric nature of the jurors themselves, or wording of the juries’ decision rules, and the “output” variable of the jury’s decision, but rather based on the internal nature of jurors’ discourse. This is a radically different focus from traditional studies comprising mock juries, one enabled by use of real deliberations for comparative evaluation.